2001
DOI: 10.2460/ajvr.2001.62.398
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriologic and histologic features in mice after intranasal inoculation of Brucella melitensis

Abstract: Changes in the spleen and liver increased with increases in dose and with increased time following intranasal inoculation with B melitensis 16M. Surprisingly, histologic changes were not observed in the lungs of inoculated mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 30 publications
5
40
0
Order By: Relevance
“…In addition, in this study, neither neutrophil influx nor significant histopathological changes were observed in the ileum or colon. Conversely, histopathological lesions observed in the spleen and liver, including neutrophilic infiltrate and granulomas were similar to the lesions described in mice inoculated by other routes of infection (19,36).…”
Section: Discussionsupporting
confidence: 78%
“…In addition, in this study, neither neutrophil influx nor significant histopathological changes were observed in the ileum or colon. Conversely, histopathological lesions observed in the spleen and liver, including neutrophilic infiltrate and granulomas were similar to the lesions described in mice inoculated by other routes of infection (19,36).…”
Section: Discussionsupporting
confidence: 78%
“…Brucella establishes a stealthy infection in mice and constitutes an interesting experimental model that can be used to analyze the relationships between hosts and intracellular stealth pathogens (46,47). Although the aerosol route is a common cause of infection in nature (1), a relatively limited number of Brucella studies (20,22,36,37,48,49) investigated the protective immune response following respiratory infection. In this study, we analyzed the progression of B. melitensis in the lungs, spleen, and liver of C57BL/6 mice, as well as the nature of the protective immune response following primary and secondary i.n.…”
Section: Discussionmentioning
confidence: 99%
“…infection was analyzed previously by several research groups (22,36,37). However, because the infectious dose, the origin of the mice, and the conditions in the animal facility could influence the course of the infection, we began by establishing the kinetics of infection under our laboratory conditions.…”
Section: Intranasal Inoculation Leads To Slow Dissemination Of Brucelmentioning
confidence: 99%
“…The genotypes G1, G4, G7, G8, G9, and G10, comprising branch 1 of the dendrogram drawn for the Peruvian isolates, were isolated almost exclusively from adult patients, and a relatively high proportion of the patients infected with the four genotypes G2, G3, G5, and G6 comprising branch 2 presented with splenomegaly and/or hepatomegaly. Studies of mice may help to elucidate differences in organ tropism and pathological effects (30).…”
Section: Gender and Risk Of Infectionmentioning
confidence: 99%